Ảnh hưởng của chất mang đến tính chất của xúc tác NiO trong phản ứng oxi-đehiđo hóa n-butan trong môi trường có CO2 - Lộc và cộng sự, Lưu Cẩm (Vietnam Journal of Chemistry, 2014)
Oxidative dehydrogenation of n-butane to butene on NiO based catalysts with the presence of carbon dioxide was studied. The phase structure of NiO has been found to depend on the nature of carrier as well as on its content. The determining factors in activity and selectivity of the studied catalysts are NiO-support interaction, reducibility of NiO and their acidic properties. On each carrier the optimal content of NiO for giving the best catalytic perfomence is as follows: 7wt.% on Al2O3, 8wt.% on SiO2, 4wt.% on active carbon and 5wt% on HZSM-5. About 38% of butane conversion and 71% of butenes selectivity were observed on 5% NiO/HZSM-5(200). Optimal conditions of the reaction are: mol ratio n-C4H10 : CO2 = 1:5 and 1:2, temperatures: 625 and 500oC for catalysts on HZSM5 and for the rest, correlatively.